Model Pembelajaran Mind Mapping untuk Meningkatkan Kemampuan Meng-I’rab Kalimat Bahasa Arab - Khairy Abusyairy; Nur Ajmi; Syarifaturrahmatullah Syarifaturrahmatullah (Faculty of Education and Teacher Training of UINSI Samarinda, 2022)
Learning I'rab Arabic sentences is still one of the problems that students often experience, including at Madrasah Aliyah Sabilarrasyad Samarinda. To overcome this the researcher offers a Mind Mapping learning model to improve the ability to I'rab Arabic sentences. This study aims to determine whether the Mind Mapping learning model is effective in improving the ability to I'rab Arabic sentences of students at Madrasah Aliyah Sabilarrasyad Samarinda. This research is a quantitative research, with the type of experimental research in the form of Quasi Experimental Type Nonequivalent Control Group Design. The sample of this study was class XI IPA-1 which consisted of 18 students as the control group and class XI IPA-2 which consisted of 16 students as the experimental group. The instruments of this study were in the form of learning achievement tests and observation sheets. Based on the research results, the experimental class obtained an average pre-test score of 32 while the control class obtained an average value of 59.8. On the average post-test score, the experimental class obtained an average value of 46.8 and the control class obtained an average value of 54.4. The experimental class experienced an increase in the average value of 14.8 while the control class experienced a decrease in the average value of 5.4. The results of data analysis using the paired sample t test showed that the significance value (2-tailed) for the experimental class was 0.006 <0.05, this can be said that Ha is accepted and H0 is rejected. And based on the results of the calculation of the N-Gain Score, it shows that the average value of the N-Gain score for the experimental class is 0.22 which is included in the low category with a minimum N-Gain score of -0.20 and a maximum of 0.71. So it can be concluded that the Mind Mapping learning model is effective in the low category in improving the ability to I'rab Arabic sentences of students at Madrasah Aliyah Sabilarrasyad Samarinda.